2018
DOI: 10.1016/j.nut.2018.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Physiological effects of a short-term lifestyle intervention based on the Mediterranean diet: comparison between older and younger healthy, sedentary adults

Abstract: Improvements in physiological function were observed after a short-term dietary intervention based on the MD in a younger population. These were not statistically matched in an older group. Our findings suggest that different durations should be applied when designing dietary interventions in different age groups, with expectations in physiological improvement differing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…For the purposes of this study, we concentrated on endothelial dysfunction, as it is a common phenomenon of all major CVD risk factors (e.g., high blood cholesterol, hypertension, diabetes, etc.). To determine cutaneous microvascular function, we used LDF, combined with local heating of the skin, as previously described in the literature [3]. This allows us to obtain information primarily on neurone-mediated axon reflex function (initial peak; [19]) and NO bioavailability (secondary rise and plateau phase; [19]).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…For the purposes of this study, we concentrated on endothelial dysfunction, as it is a common phenomenon of all major CVD risk factors (e.g., high blood cholesterol, hypertension, diabetes, etc.). To determine cutaneous microvascular function, we used LDF, combined with local heating of the skin, as previously described in the literature [3]. This allows us to obtain information primarily on neurone-mediated axon reflex function (initial peak; [19]) and NO bioavailability (secondary rise and plateau phase; [19]).…”
Section: Methodsmentioning
confidence: 99%
“…This allows us to obtain information primarily on neurone-mediated axon reflex function (initial peak; [19]) and NO bioavailability (secondary rise and plateau phase; [19]). Tests in both groups were conducted in temperature-controlled rooms, with an ambient temperature of 22–24 °C, as previously described by our lab [3]. Tests in all participants were undertaken in the upper right forearm in skin sites without visible veins, body hair, and damaged or irritated skin.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The multicenter trial in Spain, involving older high-risk persons without cardiovascular disease showed, that an energyunrestricted MedDiet supplemented with either extra-virgin olive oil or nuts has a better effect on the incidence of major cardiovascular events over a period of 5 years than a low-fat diet [8]. Recent intervention study have shown statisticallysignificant improvements in axon-mediated microvascular vasodilation and endothelialmediated nitric oxide synthesis in the younger group of patients after 4 week application of MedDiet [9].…”
Section: Introductionmentioning
confidence: 99%